O processo de participação popular no planejamento urbano: considerações sobre o acesso à participação - Ribeiro, Milena Luiza (Universidade Federal do Tocantins, 2022)
The focus of this work is the search for an understanding of the social effects of the implementation of traditional participatory instruments, predominantly in face-to-face formats, and the limitations that the conditions of access can impose on them. In this sense, it is evident that popular participation, with the capacity to influence politically and administratively, depends not only on the existence of participatory mechanisms and institutions, but also on the offer of conditions for citizens to interact and deliberate about collective issues within the city territory. Thus, it was established as a general objective of this research to understand the relations between the urban accessibility to public facilities considered for the participation actions carried out during the elaboration of the Municipal Participative Master Plan of Paraíso do Tocantins with the characteristics of the participants and the participative process. For this, the methodology used had a mixed approach with quali and quantitative methods and was divided into four stages - (i) bibliographic and documental research, (ii) data collection, (iii) spatialization and data treatment and (iv) analysis of the results. As a result, it can be inferred that the groups that have more resources such as time, income and education have fewer types of access limitations, and, therefore, are more likely to participate. Thus, it is observed that the profile of popular participation is linked to the profile of individuals with higher levels of urban accessibility, specifically in the case of Paraíso do Tocantins, the groups that use individual transportation are the most favored, while those who use public transportation and/or non- motorized transport have considerable restrictions.